2011
DOI: 10.1007/s10164-011-0288-7
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous tendencies in the round-eared sengi: a male’s perspective

Abstract: Although monogamy is interpreted as riskadverse strategy by reducing intra-sexual conflicts, most pair-living males increase their reproductive success by engaging in extra-pair copulations. However, little is known about costs involved in such extra-pair attempts from the male's perspective. We investigated promiscuous tendencies of paired Macroscelides proboscideus (roundeared elephant-shrew or round-eared sengi), a pair-living small mammal occurring in southern Africa. In particular, we measured potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A male Rhynchocyon chrysopygus chased the female and then copulated with her during 2 s with five rapid copulations. Schubert et al (2012) found in captive experiments that female Macroscelides proboscideus showed as many sexual interactions with a neighboring male as with her pair partner, and that males actively aimed to mate with non‐pair neighboring females. In an unpublished poster on a study using micro‐satellites to determine paternity in Macroscelides proboscideus , Peffley et al (2009) found for the population studied by Schubert et al (2009) that only two out of six mother‐offspring families resulted from serially monogamous mating.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A male Rhynchocyon chrysopygus chased the female and then copulated with her during 2 s with five rapid copulations. Schubert et al (2012) found in captive experiments that female Macroscelides proboscideus showed as many sexual interactions with a neighboring male as with her pair partner, and that males actively aimed to mate with non‐pair neighboring females. In an unpublished poster on a study using micro‐satellites to determine paternity in Macroscelides proboscideus , Peffley et al (2009) found for the population studied by Schubert et al (2009) that only two out of six mother‐offspring families resulted from serially monogamous mating.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, both sexes defend a territory and are very aggressive towards conspecifics of the same sex (FitzGibbon, 1997; Rathbun, 1979). Schubert et al (2012) found in captive experiments no evidence for pair‐bonding, but individuals of both sexes readily interacted with opposite sex conspecifics with which they were not paired.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations